(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
This article talks about the credit-module system of higher education in our country, its introduction, as well as the organization of the educational program structure in this educational system. This article can be used by representatives of the relevant field as theoretical and methodological information.